A Qualitative Analysis of Determinants of Premarital Sex among Students in Selected Secondary Schools in Kaduna State, Nigeria - James, Amos Akpokos; Baduku, Silas Anthonia (NIU Journal of Social Sciences, 2020)
Several studies have reported the existence of  premarital sex among secondary school students in Nigeria. Although several quantitative studies in Nigeria have identified some of the determinants of premarital sex, only few have systematically examine from the students perspective what are their motivation for engaging in premarital sex. Specifically therefore, the objective of this study is to explore the factors which influence the initiation of premarital sex among secondary school students in Kaduna State. Using the qualitative approach, this study collected data from 16 focus group discussions held among unmarried 16 – 19 year-old secondary school students. Some of the factors identified include, transactional sex, the influence of western culture and media, non-adherence to religious injunctions, proof of affection or love for boy or girl friend as well as the influence of friends or peers. Arising from the findings of this study it is recommended that parents should strive to teach their children some important aspects of their culture especially that which concerns morality and chastity as a means of curbing the negative influence of western culture on adolescents’ sexual behaviour. Keywords: Determinants, premarital sex, Students, Secondary School,